2008
DOI: 10.1007/s00259-008-0949-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term practice and task complexity on brain activities when performing abacus-based mental calculations: a PET study

Abstract: In conclusion, after intensive training and practice, the neural pathways in an abacus expert have been connected more effectively for performing the number encoding and retrieval that are required in abacus tasks, resulting in exceptional mental computational ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
4
21
0
Order By: Relevance
“…The present result is consistent with previous functional imaging studies that reported activation in the SPL during mental calculation and digit memory tasks in abacus users (Tanaka et al, 2002; Hanakawa et al, 2003; Chen et al, 2006; Wu et al, 2009). It is possible that a spatial representation of numbers is developed through abacus practice, which involves rule-based visuo motor processing, and utilized in mental calculation and digit memory tasks, because it is more efficient to mentally manipulate large numbers using a spatial representation than a sequentially organized phonological representation (Hatano et al, 1977; Hatano and Osawa, 1983 Hatano et al, 1987; Hatta et al, 1989; Hishitani, 1990; Tanaka et al, 2008; Frank and Barner, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present result is consistent with previous functional imaging studies that reported activation in the SPL during mental calculation and digit memory tasks in abacus users (Tanaka et al, 2002; Hanakawa et al, 2003; Chen et al, 2006; Wu et al, 2009). It is possible that a spatial representation of numbers is developed through abacus practice, which involves rule-based visuo motor processing, and utilized in mental calculation and digit memory tasks, because it is more efficient to mentally manipulate large numbers using a spatial representation than a sequentially organized phonological representation (Hatano et al, 1977; Hatano and Osawa, 1983 Hatano et al, 1987; Hatta et al, 1989; Hishitani, 1990; Tanaka et al, 2008; Frank and Barner, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, activity in the left SPL ( x  = −20, y  = −66, z  = 66; t  = 3.60, cluster size = 10, p svc < 0.05) was significantly greater at 13 months compared with 6 months after her stroke (Figure 6B). Activity in the left SPL was observed in the previous functional imaging studies of mental calculation tasks in abacus experts (Hanakawa et al, 2003; Chen et al, 2006; Wu et al, 2009). These functional MRI results were very consistent with the patient’s subjective report that she was able to shift the calculation strategy from a phonological – based to a mental abacus – based strategy according to her level of recovery from the stroke.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Experiment 1). Imaging studies indeed showed that the mental abacus operation is associated with enhanced activity in the brain areas relevant for visuospatial information processing (e.g., Hanakawa, Honda, Okada, Fukuyama, & Shibasaki, 2003;Wu et al, 2009). Hence, the distinct Chinese training regimens may lead to distinct mental processes and representations across operations.…”
Section: Discussionmentioning
confidence: 99%